How Does Scaffold Porosity Conduct Bone Tissue Regeneration?. Issue 10 (26th July 2021) - Mohammadi, Hossein; Sepantafar, Mohammadmajid; Muhamad, Norhamidi; Bakar Sulong, Abu
Abstract : Pores play a crucial role in bone regeneration as they allow the exchange of nutrition and oxygen, expulsion of waste products, and bone tissue and vascular ingrowth through the scaffold. From a mechanical aspect, the overall porosity is more effective compared to the pore size and interconnectivity, and pore size and interconnectivity impose the highest influences on the biological performances of the scaffold. Porosity and pore interconnectivity affect scaffold permeability controlling the rate of de novo tissue formation, whereas pore size and geometry conduct the osteogenesis. In such a theory, macropores and micropores have district advantages and their coexistence causes more preferable results. Herein, the most recent findings about the quality of pores and their roles in bone tissue regeneration are objectively reviewed. Abstract : The proper scaffold design with optimized properties can play an important role in successful bone tissue regeneration. Herein, the effects of porosity, pore size, and pore interconnectivity on the properties of bioceramic scaffolds are discussed. The porosity of above 50–70%, pore size of 320–600 μm, and pore interconnectivity of 30–90% may suggest better osteogenesis and angiogenes.